The importance of including secondary effects when defining the system boundary with life cycle perspective: Case study for design of an external wall. (1st February 2017) - Ylmén, Peter; Berlin, Johanna; Mjörnell, Kristina; Arfvidsson, Jesper
Abstract: Life cycle assessment and life cycle cost analysis are suitable tools in trying to minimize environmental impact and cost. To get reliable results it is crucial to set up correct system boundaries for the investigation, but it is often difficult to understand a complex products system because of the cascade effects of consequences that can be induced even by small changes. In this paper the effects and consequences evaluation (ECE) method is introduced to systematically identify and organize the effects and consequences for a design change of parts of a complex system. The method is applied in a case study of external wall insulation for a new building to investigate the importance of correct system boundaries. Using the methodical approach in identifying all significant consequences showed that unexpected unit processes can be important when deciding on the relevant system boundary. We also conclude that such processes can have a significant impact on the final results by calculating the change in global warming potential and life cycle cost for the processes affected by the design option. Highlights: Studied how to set up correct technical system boundary for complex products. Focused on how to identify processes and their connections. Developed method effect and consequences evaluation (ECE). Case study on external wall design for building.